2014
DOI: 10.5603/cj.a2013.0126
|View full text |Cite
|
Sign up to set email alerts
|

Is metabolic syndrome related with coronary artery disease severity and complexity: An observational study about IDF and AHA/NHLBI metabolic syndrome definitions

Abstract: Background: The aim of the present study was to assess the relation between metabolic syndrome (MS) and coronary artery disease (CAD) complexity, assessed by (p = 0.168, z = -1.38). The systolic blood pressure (p < 0.001, B = 0.354, 95% CI = -0.308 to 0.228), diastolic blood pressure (p = 0.006, B = -0.194, 95% CI = -0.333 to -0.056), age (p = 0.014, B = 0.147, 95% CI = 0.029 to 0.264), left ventricular ejection fraction (p = 0.031, B = -0.150, 95% CI = -0.286 to -0.014), waist/hip circumference (p < 0.001,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Aykan AC et al studied 'Is metabolic syndrome related with CAD severity and complexity: An observational study about IDF and AHA/NHLBI metabolic syndrome definitions' and found MS is associated with the presence and complexity of CAD. 5 Rana et al also reported more CAD in DM versus non-DM individuals [SVD (19 vs. 14%), DVD (9 vs. 7%), and TVD (9 vs. 5%) (P < 0.0001 for all)]. 6 Others have also observed similar findings.…”
Section: Resultssupporting
confidence: 59%
“…Aykan AC et al studied 'Is metabolic syndrome related with CAD severity and complexity: An observational study about IDF and AHA/NHLBI metabolic syndrome definitions' and found MS is associated with the presence and complexity of CAD. 5 Rana et al also reported more CAD in DM versus non-DM individuals [SVD (19 vs. 14%), DVD (9 vs. 7%), and TVD (9 vs. 5%) (P < 0.0001 for all)]. 6 Others have also observed similar findings.…”
Section: Resultssupporting
confidence: 59%
“…Additionally, the participants were all Southeast Chinese males, who have unique dietary habits and heredity features. Previous studies have indicated that varying definitions of MetS and different races might influence clinical outcomes 24 26 and thus partially explained the differences between the present study and others. Furthermore, the synergistic effect of MetS was determined using all of its components, which not only have complicated mechanisms but also are far from clear.…”
Section: Discussioncontrasting
confidence: 67%
“…First, we chose the Chinese criteria for MetS in this study. Using different criteria would likely generate slightly different incident rates of MetS that may influence the results of clinical outcomes [ 8 , 38 ]. Secondly, short follow-up time (5 years) and a relatively small sample size of MetS patients ( n = 221) may constitute other limitations of our study.…”
Section: Discussionmentioning
confidence: 99%